Modifications to the Conventional Nanoprecipitation Technique: an Approach to Fabricate Narrow Sized Polymeric Nanoparticles - Moorthi Chidambaram; Kathiresan Krishnasamy (Tabriz University of Medical Sciences, 2014)
Purpose: Nanoprecipitation is the convenient and commonly used method for the preparation of polymeric nanoparticles around 170 nm but yield particles with broad distribution, which require filtration step to produce particles with narrow distribution. Hence, the primary aim of the present study was to implement few modifications to the conventional nanoprecipitation method to reduce the mean particle size less than 150 nm and to produce particles with narrow distribution without filtration step. Methods: Eudragit E 100 nanoparticles were prepared using modified nanoprecipitation method 1 and 2. Prepared nanoparticles were characterized for the mean particle size, surface area and uniformity. Results: Eudragit E 100 nanoparticles prepared using modified nanoprecipitation method 1 has shown a mean particle size of 196 nm with surface area of 50.9 m2g-1 and uniformity of 0.852 whereas, Eudragit E 100 nanoparticles prepared using modified nanoprecipitation method 2 has shown a mean particle size of 114 nm with surface area of 57.9 m2g-1 and uniformity of 0.259. Conclusion: Modification to the conventional nanoprecipitation method (method 2) has produced mean particle size less than 150 nm and produced nanoparticles with narrow distribution without filtration step.